Multimedia Development of Pictionary Games with a Contextual Teaching and Learning (CTL) Approach in Improving Mufradat Mastery of Class IV Students at MIS Darussa'adah Bunobogu - Fatmawati, Rika (Al-Muyassar: Journal of Arabic Education, 2024)
This research aims to produce a product in the form of a multimedia pictionary game using the CTL approach as well as to determine the effectiveness of using this multimedia in improving the mastery of the mufradat of students in class IV at MIS Darussa'adah Bunobogu. The development of the multimedia pictionary game with the CTL approach uses the research and development (R&D) research method. The development stages carried out in this research are ADDIE or what is known as analysis, design, development, implementation and evaluation. Initial product development was based on needs analysis and then validated by 3 experts, namely material experts, media experts and language experts. The results of this development research are multimedia products for pictionary games using the CTL approach which have been tested for their suitability by media experts, linguists, material experts and students as media users. Overall validation results show good results, namely getting a very decent category with details: Material experts get a score of 96%, media experts get a score of 96%, and language experts get a score of 96%. As for the feasibility data, according to the students, they got a score of 98% and according to the teacher they got a score of 91%. Based on these values, it can be concluded that the multimedia pictionary game with the CTL approach will be effectively used to improve the mastery of the mufradat of class IV students at MIS Darussa'adah Bunobogu.Keywords: Development, Multimedia Pictionary Game, CTL Approach, Mufradat.